Validation of a compact microwave imaging system for bone fracture detection - Santos, K. C. (2023)
This work presents a systematic evaluation of the effectiveness of an air-operated microwave imaging (MWI) system for detection of arbitrarily oriented thin fractures in superficial bones, like the tibia. This includes the proposal of a new compact, portable setup where a single Vivaldi antenna performs a semi-cylindrical scan of the limb. The antenna is operated in monostatic radar mode, near the skin but without contact, thus ensuring hygiene and patient comfort during the exam. The image is reconstructed using a wave-migration algorithm in the frequency domain combined with an adaptative algorithm based on singular value decomposition to remove the skin artifact, dealing with non-uniform bone profile and tissue cover. The study investigates the system resolution, the robustness of the method to the uncertainty of the permittivity and thickness of the involved tested tissues, as well as the robustness to involuntary patient movement. The experimental validation was performed for the first time on an integral ex-vivo animal leg, with all tissues present, including skin and fur. It confirmed both the effectiveness of the method, and the feasibility of the setup.